Faktor-Faktor yang Mempengaruhi Penutupan Rute Penerbangan Batam-Rengat - Arif Nurrahman; Dewanti Dewanti; Sigit Priyanto (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
One of the pioneer flight route approved by Communication Ministry in 2018 is Batam-Rengat route. In progress, the pioneer route changed into commercial route, signed by initiation commercial company of Wings Air in August 2018. However, in August 2019, the Wings Air Company did not offer the route to the public. Finally, now, there is no flight service provided to the route, which is detrimental to people who need air transportation on that route. For the reason, it is needed to conduct research to express significance behind the closing event of the flight route. This study aimed to analyze the process of Batam-Rengat route progress from 2018 to 2019 and identify factors that affecting the closure of the Batam-Rengat flight route in 2019. Method used in this study was qualitative study with case study. Information was chosen according to specific criteria and data were collected by in-depth interview and secondary data request to relevant institutions/organizations. Hereinafter, interview data were reduced and classified according to specific themes. Furthermore, primary and secondary data were compiled into a unit to make description of activity event of Batam-Rengat route flight from 2018 to 2019. Times series analysis was used to find description of route progress process from the pioneer flight to commercial flight, and factors analysis was used to identify the factors affecting the route closure. The results of time series analysis indicate that the pioneer flight operated during six months from February 2018 to July 2018; then, along with the commercial flight for five months from August 2018 to December 2018. From January 2019 to June 2019, there was only one flight service, namely, commercial flight by the Wings Air. The results of factor analysis indicate the closure of the Batam-Rengat commercial route is influenced by passenger demand, flight schedules, airplane fares, and demand patterns. This study found other findings, namely the Japura-Padang flight route has good market potential and community/business participation efforts in Indragiri Hulu to help the occupancy rate of aircraft on the Batam-Rengat flight route